Perspectives on Regulation Adaptation in Multi-Agent Systems: from Agent to Organization Centric and Beyond - Yan, Elena; Nardin, Luis G.; Hübner, Jomi F.; Boissier, Olivier; Sichman, Jaime S. (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2025)
In Multi-Agent Systems (MAS), the regulation of agents aims to define a balance between the control of the system and the agents’ autonomy. The ability of a MAS to adapt its regulations at run-time is an important feature that enables it to be flexible to changing situations. There is no unique approach to designing such ability. In this paper, we discuss the different options along the multi-agent oriented programming dimensions, i.e., agent, environment, interaction, and organization. We show that regulation adaptation can be managed within a single dimension or distributed in multiple dimensions. We use a case study in the manufacturing system domain to motivate the regulation adaptation in each of these dimensions.